Maneuvering on non-Newtonian fluidic terrain: a survey of animal and bio-inspired robot locomotion techniques on soft yielding grounds - Godon, Simon; Kruusmaa, Maarja; Ristolainen, Asko (Frontiers in Robotics and AI, 2023)
Frictionally yielding media are a particular type of non-Newtonian fluids that deform significantly under stress and do not recover their original shape. For example mud, snow, soil, leaf litters or sand are such substrates because they flow when stress is applied but do not bounce back when released. Some robots have been designed to move on those substrates. However, compared to moving on solid ground, significantly fewer prototypes have been developed and only a few prototypes have been demonstrated outside of the research lab. This paper surveys the existing biology and robot literature to analyse principles of physics facilitating motion on yielding substrates. We categorise animal and robot locomotion based on the mechanical principles and then further on the nature of the contact: discrete contact, continuous contact above the material, or through the medium. Then, we extract the different hardware solutions and motion strategies enabling the different robots and animals to progress. The result reveals which design principles are more widely used and which may represent research gaps for robotics. We also discuss that higher level of abstraction helps transferring the solutions to robotics domain also when the robot is not explicitly meant to be bio-inspired. The contribution of this paper is a review of biology and robotics literature for identifying locomotion principles that can be applied for future robot design in yielding environments, as well as a catalogue of existing solutions either in nature or man-made, to enable locomotion on yielding grounds.